1998
DOI: 10.2105/ajph.88.3.357
|View full text |Cite
|
Sign up to set email alerts
|

State funding of comprehensive primary medical care service programs for medically underserved populations.

Abstract: OBJECTIVES: This study examined the availability of state funding for comprehensive primary care programs and the need for primary care subsidies for medically underserved communities. METHODS: A brief questionnaire was used to ask health agencies in all 50 states whether their state funded a program that met our definition of comprehensive primary medical care practice programs. An in-depth written survey instrument was then administered to the states with programs. RESULTS: Almost half of all states provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…(Ware, Kosinski, and Keller 1996) Community‐and state‐level data were obtained from a number of sources (see Table 1) and merged in with CTS data. Measures of the strength of the local safety net were per capita visits to community and migrant health centers (CMHCs), per capita visits to public and teaching hospital outpatient departments, per capita number of physicians (generalist or all patient care physicians) in the community, state and federal funding for primary care services for the medically underserved (Rosenbaum et al 1998), and mean hours per month of charity care reported by physicians in the community responding to the CTS physician survey (Cunningham et al 1999). Social capital measures were race‐specific Gini indices of income inequality and housing segregation (Harrison and Weinberg 1990), plus community‐level rates of being uninsured.…”
Section: Methodsmentioning
confidence: 99%
“…(Ware, Kosinski, and Keller 1996) Community‐and state‐level data were obtained from a number of sources (see Table 1) and merged in with CTS data. Measures of the strength of the local safety net were per capita visits to community and migrant health centers (CMHCs), per capita visits to public and teaching hospital outpatient departments, per capita number of physicians (generalist or all patient care physicians) in the community, state and federal funding for primary care services for the medically underserved (Rosenbaum et al 1998), and mean hours per month of charity care reported by physicians in the community responding to the CTS physician survey (Cunningham et al 1999). Social capital measures were race‐specific Gini indices of income inequality and housing segregation (Harrison and Weinberg 1990), plus community‐level rates of being uninsured.…”
Section: Methodsmentioning
confidence: 99%
“…However, international differences also exist in the extent of the coverage of populations with strong primary health care systems 19. Despite this, much can be learned from different systems about cost effective methods of organising health care, and much of Europe is observing developments in the NHS with interest.…”
mentioning
confidence: 99%
“…Though decentralization is often portrayed as a largely technical matter (5,6,10,11), we argue that the political context in which decentralization takes place frames its implementation. In the United States, for example, it has recently been demonstrated that politically determined underfunding-not technical failures-mars the ability of decentralized health services to provide high-quality, comprehensive, accessible care for the medically underserved (12,13).…”
mentioning
confidence: 99%